Prospective customers’ behavioural intention of Islamic microfinance services in Bangladesh - Ahmed, Selim; Islam, Rafikul; Al-Asheq, Ahmed (Universiti Malaya Press, 2021)
The present study investigates behavioural intention of the prospective customers on Islamic microfinance services in Bangladesh based on demographics such as gender, age, education, and family size. This study used self-administered survey questionnaire to determine the intention of Islamic microfinance services based on five variables, namely subjective norm, attitude towards behaviour, behavioural intention, normative belief, and behavioural belief. A total of 450 questionnaires were distributed out of which 326 responses were received (72.44%). The findings of this study indicate that male respondents have more behavioural intention on Islamic microfinance services than female respondents. On the other hand, female respondents have better behavioural belief on Islamic microfinance services compared to male counterparts. The findings also indicate that those respondents who studied up to secondary school level would like to take opinions from family members and friends to use Islamic microfinance services. The present research findings offer some important implications for Islamic microfinancial services providing institutions, practitioners and policy makers. The findings of this study are expected to reflect suggestive steps to increase the degree of behavioural attitude in using Islamic microfinance services.